Sobrevivência, crescimento, parâmetros metabólicos e enzimáticos em jundiás (Rhamdia quelen) expostos ao cobre - Silva, Vera Maria Machado da (2006)
The aim of this study was to determine the mean lethal concentration (96 h) for waterborne copper (LC50), as well as the effect of the exposure to copper on growth, metabolic parameters (glycogen, glucose, lactate, and protein) in some tissues, activity of acetylcholinesterase (AChE) (brain and muscle), amylase and maltase (intestine) in silver catfish (Rhamdia quelen). The LC50 for copper was 0.4 mg/L. On growth experiments fish were exposed to 10 and 20% LC50, i.e., 0.04 and 0.08 mg/L respectively. Exposure to copper did not change growth parameters (weight, length and biomass). In the liver, lactate levels increased in juveniles exposed to 0.04 mg/L and decreased in those maintained at 0.08 mg/L, while protein levels decreased in those exposed to both concentrations compared to unexposed specimens. Glycogen levels in the muscle were lower in fish exposed to both concentrations, glucose and lactate were higher in those exposed to 0.04 mg/L and decreased in juveniles maintained at 0.08 mg/L, while protein was higher in those exposed to 0.08 mg/L. Glucose and lactate plasma levels were higher in juveniles exposed to 0.04 mg/L, but protein levels were lower in those maintained at both copper concentrations. Amylase activity was lower in juveniles exposed to both concentrations, but maltase was higher in those exposed to 0.04 mg/L than control group. Brain AChE activity was lower in fish exposed to both concentrations while muscle AChE activity was not affected after 45 days of exposure. It can be concluded that copper can change several metabolic parameters and enzymes of toxicological and feeding interest even at sublethal concentrations.